Shaping the online public debate: The relationship between the news framing of the expropriation of YPF and readers’ comments - Muñiz, Carlos; Alvídrez Villegas, José Salvador; Téllez, Nilsa Marlen (2015)
This article examines how the expropriation of oil company YPF by the Argentine government in April 2012 was framed by Spanish digital newspapers, and whether the treatment of this issue was transferred from the media to the audience. Using the theoretical approach of framing, we analyzed the news coverage of this event to find out whether the event was reported from a strategic game frame or an issue frame. Additionally, the comments posted by the news readers were analyzed to ascertain whether there was a relationship between the frames used by the media and the latent opinion frames in the discourse of these news readers. The results show a higher presence of the issue frame in the coverage of the expropriation of YPF, whereas no significant relationship was found between the media frames and the latent frames in the readers’ opinions. Conversely, a significant relationship between these two types of frames (strategic game and issue frames) was found both inside the news content and in the readers’ comments.